Pengaruh Media Film Terhadap Minat Belajar dan Kemampuan Memahami Isi Cerita Siswa Sekolah Dasar - Endrawati Endrawati (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyse the influence of the use of film media on learning interest and the ability to understand the content of students' stories in learning Indonesian language in grade VI of SDN 011 Desa Baru. This study uses a quantitative approach with a quasi-experimental design in the form of a one-group pretest-posttest design. The subjects of the study were all grade VI students totalling 36 students and were determined by saturated sampling technique. Data collection was carried out through learning interest questionnaires, ability tests to understand the content of stories, and observation of student activities during the learning process. Data were analysed using descriptive and inferential statistics by peer-sample t-test after meeting the prerequisite tests of normality and homogeneity. The results of the study show that the use of film media has a significant influence on increasing learning interest and the ability to understand the content of students' stories. Students become more enthusiastic, active, and able to understand story elements, plots, characters, settings, and moral messages more deeply after learning using film media. The novelty of this research lies in integrating the measurement of learning interest and simultaneous understanding of story content through film media in the context of learning Indonesian in elementary schools. The practical implications of this study show that film media can be used as an alternative, effective, engaging, and contextual learning medium. The contribution of this research is expected to be an empirical reference for teachers and education practitioners in developing innovative Indonesian language learning and oriented towards improving the quality of student learning processes and outcomes.